FEATURES OF DESIGN ADVERTISING POSTERS OF MODERN COMPUTER GAMES - Хиневич, Р. В.; Васильєва, О. С.; Жиденко, А. І. (Art and Design, 2019)
Consider posters as a means of advertising, artistic techniques and design solutions were used when creating them. Analysis of advertising posters of modern computer games, revealing features of their design and placement of characteristic elements: the name or logo of the game, the image of the protagonist, special details, etc. An integrated approach to the study of posters of the gaming industry was used, which made it possible to establish the features of their design and compositional solutions. The method of comparative analysis of modern advertising posters are used. The article describes the features of game advertising posters, analyzed compositional techniques and tools used to implement a variety of design solutions. It has been established what information about the product is usually provided to users in advertising, the specific techniques of the graphic image and the main elements inherent in the posters of the gaming industry are defined and presented through illustrative material. Scientific novelty. The methods and means of composite solution of advertising posters of modern computer games are investigated and systematized. The features that distinguish the gaming industry posters from advertising other products are identified. Practical significance. As a result of scientific research revealed: the specific features inherent to the posters of the gaming industry, techniques of graphic representation and creation of compositions. The main elements that are used in the posters logo of the game, special details that distinguish the game or its series among others, types of compositions, lighting, angle are highlighted.